2015
DOI: 10.3928/00989134-20150804-61
|View full text |Cite
|
Sign up to set email alerts
|

CARES ® Dementia Care for Families™: Effects of Online, Psychoeducational Training on Knowledge of Person-Centered Care and Satisfaction

Abstract: Challenges to intervention use among family caregivers of individuals with dementia include availability and timing of delivery. The current study sought to determine whether an online, psychoeducational intervention for dementia family caregivers, CARES® Dementia Care for Families™ (CARES for Families), improved and enhanced dementia caregivers’ knowledge of person-centered care approaches. Forty-one family members completed pre- and posttest surveys that assessed improvement in dementia care knowledge, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 15 publications
0
47
0
1
Order By: Relevance
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total 28 original studies were identified that tested an intervention comprising solely of peer support or had a peer support component. We examined the extent, nature and distribution of the studies included in this review and determined the following: the majority of studies ( n = 12) used a trial design including randomised controlled trials, pragmatic randomised trials, randomised controlled evaluations, randomised controlled two group design or randomised pilot studies (Charlesworth et al, ; Finkel et al, ; Gaugler et al, , , , ; Gaugler, Reese, Reese, & Mittelman, ; Hayden, Glynn, Hahn, Randall, & Randolph, ; Laakkonen et al, , ; Lai et al, ; Martindale‐Adams, Nichols, Burns, Graney, & Zuber, ; Mittelman et al, ; Núñez‐Naveira et al, ; Torkamani et al, ; Wai Tong & Lee, ; Wang & Chien, ; Wang et al, ; Winter & Gitlin, ), eight studies used a pre/post‐test design (Boots, de Vugt, Withagen, Kempen, & Verhey, ; Chenoweth et al, ; Chu et al, ; Dam, van Boxtel, Rozendaal, Verhey, & de Vugt, ; Gaugler, Hobday, et al, ; Hsu et al, ; Javadpour, Ahmadzadeh, & Bahredar, ; O'Connor, Arizmendi, & Kaszniak, ), four a quasi‐experimental design (Andren & Elmståhl, , ; Easom, Alston, & Coleman, ; Marziali & Garcia, ; Pagán‐Ortiz, Cortés, Rudloff, Weitzman, & Levkoff, ), two a quasi‐experiment with mixed methods design (Baily, Kingsyon, Alford, Taylor, & Tolhurst, ; Küçükgüçlü, Akpınar Söylemez, Yener, & Işık, ) and the final two studies used mixed methods (Hattink, Droes, Sikkes, Oostra, & Lemstra, ; McKechnie, Barker, & Stott, ).…”
Section: Methodsmentioning
confidence: 99%
“…Carers Assessment of Satisfaction Index (CASI) (Nolan, Grant, & Keady, 1996) ‐ (1) Carers of Older People in Europe Index (COPE index)/ subscale Positive Aspects of Caring (PAC) (McKee et al, 2003)‐ (1) Personal Growth Index (PGI) (Ryff & Keyes, 1995)‐ (1) Satisfaction with Life Scale (SWLS) (Diener, Emmons, Larsen, & Griffin, 1985)‐ (1) Satisfaction items – likert scale (J. E. Gaugler, Hobday, et al, ) ‐ (1)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the questionnaire has been used to assess knowledge in the general population or among students (UK [12]; Norway [13]; USA [14,15,16]; South Korea [17] among health professionals and care staff [18], among psychologists [19] and it has been used as an outcome measure for validation of an online training program for care-workers [20].…”
Section: Introductionmentioning
confidence: 99%